Decreased ATF5 level contributes to improved mitochondrial function in oocytes exposed to vitrification stress - Zhou, Guizhen; Liu, Aiju; Bai, Jiachen; Liu, Hongyu; Zhu, Yixiao; Luo, Yuwen; Zheng, Lv; Hou, Yunpeng; Li, Jun; Fu, Xiangwei (Frontiers in Cell and Developmental Biology, 2024)
Mitochondrial unfolded protein response (mtUPR) plays an essential role in the response of mitochondria to stress-induced damage. Activating of transcription factor 5 (ATF5) can help to sustain mitochondrial function and regulate organelle recovery under mitochondrial stress. Vitrification is a stressor that disrupts mitochondrial activity and cell homeostasis. However, little is known about the function of ATF5 in response to the extreme biophysical and chemical stresses during oocyte vitrification. In the present study, the mitochondrial membrane potential and ATP levels were decreased in ATF5 knockdown oocytes, in line with the phenotypes observed in vitrified oocytes. In addition, ATF5 knockdown resulted in decreased mitochondrial temperature, reduced unfolded protein levels, abnormal mitochondrial dynamics (fusion and fission), and increased autophagy. Subsequent experiments indicated that mtUPR was suppressed in oocytes with ATF5 knockdown. Interestingly, ATF5 was aberrantly up-regulated in oocytes exposed to vitrification stress. Reduced ATF5 expression to a homeostatic level in vitrified oocytes led to accumulated unfolded protein levels and increased mitochondrial membrane potential. Moreover, increased mitochondrial dynamics and an increased germinal vescile breakdown (GVBD) rate were detected after in vitro maturation. Transcriptome analysis revealed that ATF5 is involved in the vitrification stress response, and ATF5 regulated the in vitro maturation potential in vitrified oocytes through the cAMP-PKA and PI3K/AKT pathways. In summary, our findings indicate that mtUPR was initiated in response to vitrification stimuli, and down-regulated ATF5 level to a homeostatic state contributes to improved mitochondrial function in oocytes exposed to vitrification stress. Our results highlight the crucial role of ATF5 in the regulation of mitochondrial function in vitrified oocytes through mediating mtUPR.